New U-series and coupled ESR/U-series dating of Hulu Cave, a key Homo erectus site in China - Qingfeng Shao; Christophe Falguères; Yunping Huang; Salah Abdessadok; Wenbo Bao; Jianing He; Xi Chen; Xianglin Zhou; Xinrui Jin; Guilan Hu; Bassam Ghaleb; Yingfei Zhang; et al. (Quaternary Science Reviews, 2026)

Macrocycle-size-modulated Cl− microenvironments in cationic mesoporous polymers for rapid capture of volatile iodine - Zhangjie Huang; Jinkai Qiu; Liang Liu; Qimeng Sun; Xiaoyong Xia; Cheng Lian; Dongyun Chen; Hua Li; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2026)

Lymph node-targeted H2S-self-releasing multifunctional prodrug for the dual remodeling of immunological and redox homeostasis in autoimmune uveitis - Qinjin Dai; Yuelan Wu; Wenbo Geng; Mengna Li; Wanyun Zhang; Yuxian Lai; Pei Zhang; Xiaoyue Zhang; Chunjiang Zhou; Yinuo Wang; Qingfeng Cao; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

ODARRL: Obstacle- and Disturbance-Aware End-to-End Residual Reinforcement Learning for Underwater Robot Trajectory Tracking with Obstacle Avoidance - Linghan Meng; Zebin Huang; Qingfeng Yao; Yunxiu Zhang; Qifeng Zhang (Journal of Marine Science and Engineering, 2026)
ROVs are essential for marine exploration and underwater operations, yet conventional teleoperation relies heavily on skilled human operators, and many autonomous methods stop at high-level planning rather than low-level actuation, limiting robustness in disturbed and cluttered environments. This paper proposes ODARRL, an obstacle- and disturbance-aware sensor-to-thruster (ST) end-to-end residual reinforcement learning framework for safe trajectory execution of underwater robots. Using a three-stage curriculum, ODARRL first acquires a basic policy from MPC demonstrations in a static obstacle-free environment, then improves disturbance-robust tracking under random currents, and finally extends to scenarios involving both currents and obstacles. A Dual-Horizon Attention Disturbance Encoder is further designed to capture current-related features from long- and short-term histories, which are fused with robot states and reference information as the input to the ST end-to-end policy. Experiments in Marine Gym with BlueROV2 Heavy demonstrate that ODARRL achieves more stable and robust trajectory tracking under random currents, reducing the mean total tracking error by 69.3%, 31.9%, 45.8%, 73.0% and 25.8% relative to the MPC-imitation policy, PPO, SAC, A2C and VNRS-SAC, respectively. With obstacles introduced, curriculum-initialized policies also exhibit higher path progress and more stable task completion during obstacle-avoidance training.

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Targeting the Wnt/β-catenin pathway: veratramine mitigates MNNG-induced gastric precancerous lesions - Pan Zhang; Xuelin Sun; Longteng Liu; Yatong Zhang; Jiaqi Bo; Wenli Huang; Yifan Na; Jingyi Zhang; Xiaoyun Qin; Qingfeng Luo (Molecular and Cellular Biochemistry, 2026)

Chloride ions accelerated the removal of naproxen in Cu(II)/peracetic acid system: Promotion of copper cycling through the formation of copper-chloride complexes - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li (Water Research, 2026)

Enhanced removal of organic pollutants and effective suppression of chlorinated/brominated by-products in heat/peroxymonosulfate system by adding sodium percarbonate - Yao Huang; Chenyu Tang; Bingyu Lu; Jianhang Li; Lukai Zhuang; Minfeng Wang; Haoqiang Tan; Qingfeng Cheng; Qingsong Li; Bo Sun; Jing Zou (Journal of Environmental Chemical Engineering, 2026)

Flow pattern regime of ventilated cavity around an axisymmetric body under a varying incoming flow velocity: an experimental study - Zichao Shao; Liang Hao; Yue Wu; Taotao Liu; Qingfeng Yang; Dongning Fan; Biao Huang (Ocean Engineering, 2026)

A novel biogas liquefaction process adopting dual nitrogen expansion cycle with carbon dioxide pre-cooling - Yanjun Huang; Qingfeng Jiang; Xiaofei Lu; Xiao Song; Jiangchao Wang; Huaibin Li (International Journal of Refrigeration, 2026)

Zinc oxide nano-priming fortifies Triticum aestivum L. against salt stress through physio-morphological, biochemical and transcriptomic responses - Muhammad Ateeq; Muhammad Azeem Ashraf; Qingfeng Dong; Hao Ren; Tauqeer Ahmad Yasir; Linzhou Huang; Liang Chen; Yin-Gang Hu (Plant and Soil, 2026)

MnO2-resistant ABTS spectrophotometry for trace permanganate - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Xuewei Yu; Bo Sun; Zhongda Yan; Haoqiang Tan; Qingfeng Cheng; Jun Ma (ENGINEERING Environment, 2026)

Childhood susceptibility to PFAS-associated endocrine disruption: NHANES age-stratified analysis and PFOS mouse model validation - Qiming Yang; Wenxin Bai; Yujun Liu; Xiuxian Huang; Bing Zou; Zubair Muhammad; Uswa Farooq; Qingfeng Zhai; Nan Liu (Reproductive Toxicology, 2026)

Two-phase structure optimization of Al-doped Ag1.995Te0.5S0.5 for improved mechanical and thermoelectric properties - Min Zhu; Xiao-Lei Shi; Hao Wu; Meng Li; Wei-Di Liu; De-Zhuang Wang; Liang-Cao Yin; Wen-Yi Chen; Yan Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2026)

Macrocyclic Schiff-base covalent organic polymers with synergistic multi-sites for high-temperature iodine/methyl iodide capture - Liang Liu; Zhonglin Ma; Jiaqing Huang; Zhangjie Huang; Jiajia Li; Jinkai Qiu; Ying Zheng; Cheng Lian; Dongyun Chen; Long Chen; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2026)

Hydrodynamics knowledge-driven path planning for safety-constrained energy-saving in amphibious unmanned ground vehicles - Jun Luo; Jing Huang; Huayan Pu; Fanglong Wang; Qingfeng Li; Gang Wang; Mingyang Liu (Ocean Engineering, 2025)

Unveiling land competition through interaction networks: A consistency-based mining and simulation model that integrates inhibiting effects of land uses - Xun Liang; Jun-Long Huang; Qingfeng Guan (Landscape and Urban Planning, 2025)

Triple-synergistic dual-macrocyclic polysulfates for efficient capture of diverse iodine species - Jiajia Li; Jiaqing Huang; Xiaoyong Xia; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

A triazine-tri-imidazole based cationic covalent organic polymer featuring high recyclability and radiation tolerance for efficient Re(Tc)O4- sequestration - Jiaqing Huang; Xiaoyong Xia; Jiajia Li; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2025)

Persistently centennial to millennial variability of Asian summer monsoon and north-south coupling during the late penultimate glacial period - Wei Huang; Zhenqiu Zhang; Kan Zhao; Yongjin Wang; Qingfeng Shao; Jinguo Dong; Xiuyang Jiang; Xiumin Zhai; Carlos Pérez-Mejías (Global and Planetary Change, 2025)

Physiological and transcriptomic responses of fall armyworm, Spodoptera frugiperda to host-plant switching - Jun Peng; Renwen Zheng; Jinyuan Zhao; Jinhui Zhang; Qianqian Li; Dongyan Huang; Xin Zhou; Lijuan Liu; Zhuocong Li; Xiaoman Ning; Sihan Lu; Qingfeng Tang (Journal of Pest Science, 2025)

A new type of triploid fish derived from female Carassius auratus red var. × male Gobiocypris rarus - Fanglei Liu; Ziyi Huang; Xuanyi Zhang; Bei Li; Lujiao Duan; Jianming Yu; Qizhi Liu; Siyang Huang; Hongwen Liu; Qiuli Liang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Effects of dietary rumen-degradable protein on the growth performance, energy, and nitrogen metabolism of dairy buffalo heifers - Qingfeng Tang; Pengcheng Shao; Chongli Wen; Zeming Bu; Guangsheng Qin; Yali Huang; Yuhong Pan; Zhipei Li; Kelong Wei; Shulu Li; Bishi Lan; Huapei Zhong; et al. (Tropical Animal Health and Production, 2025)

Gut bacteria of the fall armyworm, Spodoptera frugiperda, promote host resistance against the toxic effects of lufenuron - Qianqian Li; Renwen Zheng; Jinyuan Zhao; Sihan Lu; Yue Liu; Dongyan Huang; Jinhui Zhang; Lijuan Liu; Xin Zhou; Qingfeng Tang (Journal of Pest Science, 2025)

An Ocular Exposure Prediction for Topical Atropine in Human Using Physiologically Based Pharmacokinetic Modeling - Aole Zheng; Tian Han; Fengjiao Bu; Qingfeng He; Jianmin Shang; Paul Chi Lui Ho; Xiaoqiang Xiang; Xingtao Zhou; Taomin Huang (The AAPS Journal, 2025)

The impact of sub-pixel scale urban function on urban heat island: Insights derived from its decomposition - Qingfeng Guan; Yajun Li; Wenjia Huang; Wei Cao; Zhewei Liang; Jie He; Xun Liang (Applied Geography, 2025)

The formation and growth characteristics of an all-female hybrid crucian carp - Lujiao Duan; ChaoLiang Shen; Jingjing Lin; Xiaoxia Xiong; Huan Sun; Ziyi Huang; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Alterations in microbial community structures and metabolic function in soil treated with biological and chemical insecticides - Renwen Zheng; Jun Peng; Qianqian Li; Yue Liu; Dongyan Huang; Yangjunlu Sheng; Cui Liu; Lei Qi; Nemat O. Keyhani; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2025)

Millennial-scale hydroclimate dynamics in the Southeastern Tibetan Plateau: linkages with atmospheric circulation changes during the last glacial period - Lei Huang; Liping Zhu; Junbo Wang; Yongsong Huang; Jianting Ju; Qingfeng Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Experimental Study on the Differences in Acoustic Emission Precursor Between Rockburst and Brittle Failure Based on the Data Mining Method - Jie Sun; Dongqiao Liu; Manchao He; Qingfeng Sun; Huili Huang (Rock Mechanics and Rock Engineering, 2025)

Multi-omics reveals the molecular mechanisms of rapid growth in distant hybrid fish - Xuanyi Zhang; Fanglei Liu; Bei Li; Lujiao Duan; Jianming Yu; Ziyi Huang; SiYang Huang; Hongwen Liu; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Different ploidy-level hybrids derived from female common carp × male topmouth culter - Conghui Yang; Chenghua Dai; Qiong Liu; Yating Zhu; Xuexue Huang; Xiaowei Xu; Yi Zhou; Shi Wang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Incorporating graphene quantum dots boosts thermoelectric performance of PEDOT:PSS films - Ting Wu; Xiao-Lei Shi; Yu-Yu Deng; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Fang Yue; Pei Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2025)

Hydroclimate variability in southeastern Tibetan Plateau since the late Quaternary: Insights from hydrogen isotopes in sedimentary leaf waxes - Lei Huang; Liping Zhu; Yongsong Huang; Junbo Wang; Jianting Ju; Qingfeng Ma (CATENA, 2025)

Experimental investigation on the ventilated cavitating flow characteristics around an axisymmetric body with an unsteady ventilation - Liang Hao; Housheng Zhang; Qingfeng Yang; Taotao Liu; Biao Huang; Guoyu Wang (Ocean Engineering, 2024)

High-performance thermoelectric PEDOT:PSS fiber bundles via rational ionic liquid treatment - Yu-Yu Deng; Xiao-Lei Shi; Ting Wu; Hao Wu; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Pei Huang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Constructing local structure heterogeneity in AgNbO3-based antiferroelectrics: Achieving excellent anti-fatigue and energy storage properties - Shuaibing Gao; Zhihang Xu; Haolin Zeng; Meng Shen; Ye Zhu; Haitao Huang; Yongming Hu; Yunbin He; Qingfeng Zhang (Chemical Engineering Journal, 2024)

Stomatin-like protein 2 promotes cell proliferation and survival under 5-Fluorouracil stress in hepatocellular carcinoma - Xiaoqi Li; Yahui Zheng; Kangkang Yu; Sen Hou; Huxiao Cui; Ruiqi Yin; Yu Zhou; Qingfeng Sun; Jubo Zhang; Chong Huang (Molecular Biology Reports, 2024)

Benzo(a)pyrene exposure impacts cerebrovascular development in zebrafish embryos and the antagonistic effect of berberine - Ke Xu; Qian Wang; Ying Zhang; Yuehong Huang; Qingfeng Liu; Meng Chen; Chonggang Wang (Science of The Total Environment, 2024)

Mechanism of Self-Assembled Celastrol-Erianin Nanomedicine for treatment of breast cancer - Jiahang Tian; Kun Chen; Qian Zhang; Chong Qiu; Haibo Tong; Jingnan Huang; Mingjing Hao; Junhui Chen; Wentong Zhao; Yin-Kwan Wong; Lei Gao; Piao Luo; et al. (Chemical Engineering Journal, 2024)

Recent progress in carbonaceous materials for the hydrogen cycle: Electrolytic water splitting, hydrogen storage and fuel cells - Guanghui Xia; Habibullah; Qingfeng Xie; Qin Huang; Meitong Ye; Bingshou Gong; Rui Du; Yao Wang; Yigang Yan; Yungui Chen; Chaoling Wu (Chemical Engineering Journal, 2024)

Construction of Remote Sensing Quantitative Model for Biomass of Deciduous Broad-Leaved Forest in Mazongling Nature Reserve Based on Machine Learning - Xuehai Tang; Dagui Yu; Haiyan Lv; Qiangxin Ou; Meiqin Xie; Peng Fan; Qingfeng Huang (Journal of the Indian Society of Remote Sensing, 2024)
As an important forest type, deciduous broad-leaved forest is crucial for estimating forest carbon sequestration capacity and evaluating forest carbon balance. This study focuses on the natural deciduous broad-leaved forest of Mazongling Nature Reserve in Jinzhai County of China. WorldView-2 images were selected as data source. 36 candidate factors including vegetation indices, texture features, and topographic factors were used for modelling. Three machine learning algorithms (i.e., random forest, k-nearest neighbor, and artificial neural network) were used to establish the optimal quantitative retrieval model for natural deciduous broad-leaved biomass. Results showed that the ANN model was the best predictor with R 2 = 0.69 and RMSE = 31.53 (Mg·ha −1 ). Combining the ANN model with the complete spatial coverage of remote sensing data, we developed a distribution map of natural deciduous broad-leaved biomass in the Mazongling forest farm. The estimated average biomass of the study area was 90.34 ± 47.96 Mg·ha −1 . In addition, the influence of light saturation on model accuracy is also discussed. This study confirms that remote sensing data in temporal and spatial space can improve the model estimation accuracy.

Coupled ESR and U-series dating of the northernmost evidence of Gigantopithecus from Jianshi Longgudong site, China - Fei Han; Jean-Jacques Bahain; Qingfeng Shao; Pierre Voinchet; Fangfang Tang; Mi Zhou; Manchen Huang; Gongming Yin (Quaternary Geochronology, 2024)

Modeling the Subpixel Land-Use Dynamics and Its Influence on Urban Heat Islands: Impacts of Factors and Scale, and Population Exposure Risk - Xun Liang; Song Guo; Chunyang Huang; Bingyu Wang; Yao Xiao; Jie He; Yang Li; Mengmeng Wang; Qingfeng Guan (Sustainable Cities and Society, 2024)

Effects of different cold chain logistics modes on the quality and bacterial community succession of fresh pork - Su Wang; Dequan Zhang; Qingfeng Yang; Xiangyuan Wen; Xin Li; Tongjing Yan; Rui Zhang; Wei Wang; Kumayl Hassan Akhtar; Caiyan Huang; Chengli Hou (Meat Science, 2024)

An electrical conduction model for calcium-bearing shaly sandstone based on the effective medium Hanai-Bruggeman theory - Pengji Zhang; Yu Liang; Buzhou Huang; Fuyan Gou; Yangming An; Qingfeng Li; Hongzheng Li; Ruiyi Han (Acta Geophysica, 2024)

Forces driving ecological degradation in southern China during the MIS3: Natural or anthropogenic? - Qiong Chen; Xiaobo Huang; Hua Tu; Qingfeng Shao; Xiaoming Sun; Qiaofen Liu; Wei Wang; Zhongping Lai; Xiaoqiang Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Benthic foraminiferal assemblages in the coastal zone of the yellow river delta: Environmental significance and characteristics of microbial diversity - Shuyang Huang; Qing Li; Xiaohua Qiu; Hong You; Ruimin Lv; Wei Liu; Qingfeng Chen; Tiantian Wang; Jing Zhang; Junjian Ma; Zihao Wang; Shigang Ding (Continental Shelf Research, 2024)

Estimation of the Relative Chlorophyll Content of Carya illinoensis Leaves Using Fractional Order Derivative of Leaf and Canopy Scale Hyperspectral Data - Jiajia Xu; Genshen Fu; Lipeng Yan; Lei Yu; Fan Kuang; Qingfeng Huang; Xuehai Tang (Journal of Soil Science and Plant Nutrition, 2024)
Chlorophyll is a crucial physiological and biochemical indicator that impacts plant photosynthesis, accumulation of photosynthetic products, and final yield. The measurement and analysis of chlorophyll content in plants can provide valuable insights into their nutritional status and overall health. The non-destructive and efficient estimation of relevant plant physiological and biochemical indicators using hyperspectral technology can provide a reliable method for collecting data on nutrient levels and health status during plant growth and development. Fifty-three Carya illinoensis plants of Jiande and Changlin series known for their exceptional qualities and significant economic benefits were used as the research object for collecting their leaf and canopy hyperspectral data. Firstly, fractional order derivative (FOD) was used for spectral preprocessing. Secondly, the spectral response relationship between spectrum and relative chlorophyll content (soil and plant analyzer development, SPAD) was explored by combining single-band and two-band spectral index (normalized difference spectral index, NDSI). The correlation coefficient of Pearson correlation analysis was used to estimate the linear correlation between variables. Finally, the correlation between the spectral feature variables and SPAD was analyzed and calculated. Top 10 absolute values of the correlation coefficients were screened out as modeling variables. eXtreme gradient boosting (XGBoost) machine learning algorithm was used to construct the optimal estimation model of SPAD of Carya illinoensis leaves. Results showed that the correlation between leaf and canopy spectrum after FOD pretreatment and SPAD was substantially improved, compared with raw spectrum. FOD combined with leaf and canopy NDSI was more effective than single band in improving the correlation between spectral characteristics and target components, which was increased by 0.166 and 0.338, respectively. The leaf spectrum could estimate SPAD more accurately than that of canopy spectrum. The optimal SPAD model was the 0.5th-order derivative transformation combined with two-band leaf spectral index (NDSI) model. The R 2 P was 0.788, and the RMSEP was 0.842 in prediction set. On one hand, this study confirms the feasibility of rapid and non-destructive estimation of SPAD of Carya illinoensis leaves using hyperspectral technology. On the other hand, FOD combined with two-band spectral indices can significantly improve the response relationship between spectral characteristics and target variables, enrich hyperspectral data processing methods, and propose a novel approach for the detection of plant nutrient level and health.

Using low-protein diet in egg production for win-win of productivity and environmental benefits should be prudent: Evidence from pilot test - Meiling Liu; Shunju Geng; Qingfeng Wang; Jinqiu Mi; Lihong Zhao; Jianyun Zhang; Cheng Ji; Hongliang Wang; Qiugang Ma; Shimeng Huang (Science of The Total Environment, 2024)

Metagenomic insights into the diversity of 2,4-dichlorophenol degraders and the cooperation patterns in a bacterial consortium - Shunli Hu; Chuangchuang Xu; Yanghe Xie; Lu Ma; Qingfeng Niu; Guomin Han; Junwei Huang (Science of The Total Environment, 2024)

Environmental-friendly enzyme nanoreactors with high adsorption capacity for long-time and efficient treatment of pollutants under visible light irradiation - Shuting Huang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2024)

Understanding the mediating role of labor out-migration in household income generation and distribution under a reforestation policy in rural China - Qi Zhang; Rajesh Bista; Richard E. Bilsborrow; Zhiqiang Zhang; Qingfeng Huang; Conghe Song (Journal of Environmental Management, 2023)

The impact of ambient air pollutants on childhood respiratory system disease and the resulting disease burden: a time-series study - Wenbin Shen; Xue Li; Qingfeng Fang; Guoao Li; Wei Xiao; Yueyang Wu; Jianjun Liu; Wenlei Hu; Huanhuan Lu; Fen Huang (International Archives of Occupational and Environmental Health, 2023)

The Tartary buckwheat bHLH gene ALCATRAZ contributes to silique dehiscence in Arabidopsis thaliana - Wenjun Sun; Ying Chen; Jing Zeng; Chenglei Li; Min Yao; Moyang Liu; Zhaotang Ma; Li Huang; Jun Yan; Junyi Zhan; Hui Chen; Tongliang Bu; et al. (Plant Science, 2023)

Highly enhanced direct catalytic oxidation of cyclohexane to adipic acid with molecular oxygen: Dynamic collaboration between zeolite channel micro-environment and Au clusters - Zhiyang Zhang; Mi Hu; Qingfeng Gui; Jing Gu; Wenlong Xu; Qingbo Xiao; Wei Huang (Chemical Engineering Journal, 2023)

PneuNet: deep learning for COVID-19 pneumonia diagnosis on chest X-ray image analysis using Vision Transformer - Tianmu Wang; Zhenguo Nie; Ruijing Wang; Qingfeng Xu; Hongshi Huang; Handing Xu; Fugui Xie; Xin-Jun Liu (Medical & Biological Engineering & Computing, 2023)

Responses of Soil Humus Composition and Humic Acid Structural Characteristics to the Addition of Different Types of Biochar in Phaeozems - Qi Wang; Yingxue Zhu; Lianzhou Xu; Baiyang Chen; Chunzhu Liu; Xianfa Ma; Qingfeng Meng; Bing Liu; Zongwei Huang; Yusheng Jiao; Ye Yuan (Journal of Soil Science and Plant Nutrition, 2023)

High fructose-induced skeletal muscle insulin resistance could be alleviated by berberine via AMPD1 and ADSL - Juanjuan Cheng; Xingdong Ma; Guangtao Yan; Qiuxia Yu; Zhen Huang; Guoshu Lin; Mengyao Li; Fengkun Guan; Ziren Su; Fang Yan; Yuhong Liu; Qingfeng Xie (Food and Chemical Toxicology, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Advanced nitrogen removal performance and microbial community structure of a lab-scale denitrifying filter with in-situ formation of biogenic manganese oxides - Qingfeng Cheng; Zongyang Liu; Yang Huang; Shanshan Feng; Erdeng Du; Mingguo Peng; Jie Zhang (Journal of Environmental Management, 2023)

TRPV1 Suppressed NLRP3 Through Regulating Autophagy in Microglia After Ischemia-Reperfusion Injury - Yao Lin; Tingting Huang; Weimin Shen; Qiongyi Pang; Qingfeng Xie; Xiang Chen; Fengxia Tu (Journal of Molecular Neuroscience, 2022)

Chelerythrine Ameliorates Pulmonary Fibrosis via Activating the Nrf2/ARE Signaling Pathway - Ling Peng; Li Wen; Qingfeng Shi; Feng Gao; Bin Huang; Changming Wang (Cell Biochemistry and Biophysics, 2021)

Isolation and characterization of a recombinant Muscovy duck parvovirus circulating in Muscovy ducks in South China - Hanqin Shen; Jianfei Huang; Zhuanqiang Yan; Lijuan Yin; Qunhui Li; Qingfeng Zhou; Feng Chen (Archives of Virology, 2020)

Performance and microbial community profiles in pilot-scale biofilter for ammonia, iron and manganese removal at different dissolved oxygen concentrations - Qingfeng Cheng; Yang Huang; Lichao Nengzi; Jianying Liu; Jie Zhang (World Journal of Microbiology and Biotechnology, 2019)

Primary limitation on vegetation productivity shifts from precipitation in dry years to nitrogen in wet years in a degraded arid steppe of Inner Mongolia, northern China - Lei Huang; Dangjun Wang; Luhua Yao; Xiaoting Li; Dengke Wang; Qingfeng Du; Yong Zhang; Xiangyang Hou; Yanjun Guo (Journal of Soils and Sediments, 2019)

Effective degradation of Orange G and Rhodamine B by alkali-activated hydrogen peroxide: roles of HO2− and O2·− - Daiyao Wang; Jing Zou; Huahua Cai; Yixin Huang; Fei Li; Qingfeng Cheng (Environmental Science and Pollution Research, 2019)

Mid-late Holocene Asian monsoon evolution indicated by peat deposits in the source area of the Yellow River, northeastern Tibetan Plateau - Qingfeng Wang; Huijun Jin; Yadong Huang (Theoretical and Applied Climatology, 2018)

Increasing concurrent drought and heat during the summer maize season in Huang–Huai–Hai Plain, China - Lijun Wang; Shuhua Liao; Shoubing Huang; Bo Ming; Qingfeng Meng; Pu Wang (International Journal of Climatology, 2018)
Although an individual climate event may not be severe, the concurrence of climate events could have a significant impact on crop production. Investigating concurrent climate extremes during crop growth is important to formulate corresponding strategies for crop production. To assess the occurrence risk of concurrent drought and heat events in the Huang–Huai–Hai Plain (HHHP), China during the summer maize season, we analysed the temporal and spatial patterns of precipitation, standardized precipitation evapotranspiration index (SPEI), drought frequency, and extreme degree days (EDD) during the critical growth period. We used daily data from 41 meteorological stations in the region from 1980 to 2015. We determined that concurrent drought and heat events increased from northeast to southwest. The combined events mainly occurred during the vegetative period, and they significantly increased in 2006–2015 relative to 1981–1990. The spatial distribution of precipitation increased from northwest to southeast, while drought displayed no significant trends. The EDD displayed a rising trend and was intensified after 2000 in different growth periods. Its spatial distribution increased from east to west during the vegetative period and from northeast to southwest during the reproductive period. Although we focused on the combined extreme events for maize in HHHP, similar phenomenon should receive more attention in globally important crop areas and other ecosystems.

The Expression Patterns of Septin-9 After Traumatic Brain Injury in Rat Brain - Hui Mao; Jiao Liu; Wei Shi; Qingfeng Huang; Xide Xu; Lanchun Ni; Feihui Zou; Jinlong Shi; Debao Li; Yonghua Liu; Jian Chen (Journal of Molecular Neuroscience, 2013)